Presentation and management outcomes of Retinoblastoma among Syrian refugees in Jordan - Yousef, Yacoub A.; Abu Salim, Qusai F.; Mohammad, Mona; Jaradat, Imad; Mehyar, Mustafa; AlJabari, Reem; Al-Habahbeh, Omar; Saboubeh, Khalid; Halalsheh, Hadeel; Khzouz, Jakub; Shawagfeh, Munir; Sultan, Iyad; et al. (Frontiers in Oncology, 2023)
Purpose: The humanitarian crisis in Syria has had a profound impact on the entire region. In this study, we report the patterns of presentation and management outcomes of Syrian patients with Retinoblastoma (Rb) treated at a single tertiary cancer center in Jordan. Methods and Materials: This is a retrospective comparative study of Syrian refugees and Jordanian citizens who had Rb between 2011 and 2020. Collected data included patient’s demographics, presentation, tumor stage, treatment modalities, eye salvage rate, metastasis, and mortality. Results: Thirty Syrian refugees (16 (53%) had bilateral disease) and 124 Jordanian citizens (51(41%) had bilateral disease) were diagnosed with Rb during this period. The median age at diagnosis for refugees was 10 and 32 months for patients with bilateral and unilateral Rb consecutively, compared to 6 and 28 months for citizens. The median lag time between signs of disease and initiation of treatment was 3 months for refugees, compared to 1 month for citizens. Refugees were more likely to present with a more advanced stage (p=0.046). Out of 46 affected eyes in refugees; 32 (70%) eyes were group D or E, while out of 175 affected eyes among citizens; 98 (56%) eyes were group D or E. Therefore, refugees with Rb were more likely to mandate primary enucleation (48%) compared to citizens (25%) (p=0.003). However, out of 24 eyes among refugees who received conservative therapy, 15 (62%) eyes were successfully salvaged, while out of 131 affected eyes among citizens who received conservative therapy, 105 (80%) eyes were successfully salvaged (p=0.06). Two (7%) of the refugees and four (3.2%) of the citizens with Rb died from metastasis. Conclusion: Syrian refugees with Rb presented with more advanced disease due to delay in diagnosis and referral that increased treatment burden by decreasing the chance for eye globe salvage. However, patients who received timely intervention had a similar outcome to citizens with Rb; probably a reflection of the management of all patients at a single specialized center. We advocate for timely referral of refugees with this rare life-threating tumor to specialized cancer center for the best possible outcome.